2017
DOI: 10.1021/acs.jpcb.7b07065
|View full text |Cite
|
Sign up to set email alerts
|

Is Vitamin A an Antioxidant or a Pro-oxidant?

Abstract: Antioxidant efficiency of all-trans-retinol has been studied on the basis of characteristic thermochemical properties using density functional theory. The influence of the solvent polarity has also been evaluated. It is found that retinol may act in parallel as an effective antioxidant via H atom donating as well as a pro-oxidant in yielding reactive hydroxyl radical. In fact, the lowest values of bond dissociation enthalpy were found at the C18-H and C18-OH positions. Retinol was also determined to be a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…The liver plays a key role: Retinol is esterified to retinyl esters and stored in the stellate cells [27]. The oxidative ability of vitamin A has been the subject of much debate, with cases made for it being both antioxidative as well as pro-oxidative [28].…”
Section: Source and Physiological Rolementioning
confidence: 99%
“…The liver plays a key role: Retinol is esterified to retinyl esters and stored in the stellate cells [27]. The oxidative ability of vitamin A has been the subject of much debate, with cases made for it being both antioxidative as well as pro-oxidative [28].…”
Section: Source and Physiological Rolementioning
confidence: 99%
“…Carotenoids, as reported above, are well-known antioxidants [ 253 , 254 ]. However, research has indicated that in excess, carotenoids may have pro-oxidant effects as well [ 255 , 256 ].…”
Section: Vitamin a Functionsmentioning
confidence: 99%
“…Indeed, it has been widely accepted in the literature that the H transfer may occur via either H-atom transfer (HAT) mechanism or proton coupled electron transfer (PCET) one. [9] And the singly occupied molecular orbitals (SOMO) calculated at the TS consist in one of the most evident signals to distinguish these two processes. In fact, in HAT process the SOMO distributes along the H-atom mitigating vector from H-donor to H-acceptor.…”
Section: Formal Hydrogen Transfer (Fht)mentioning
confidence: 99%